2009
DOI: 10.1093/hmg/ddp282
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bloom syndrome protein destabilizes human gene cluster architecture

Abstract: Bloom syndrome confers strong predisposition to malignancy in multiple tissue types. The Bloom syndrome patient (BLM) protein defective in the disease biochemically functions as a Holliday junction dissolvase and human cells lacking functional BLM show 10-fold elevated rates of sister chromatid exchange. Collectively, these phenomena suggest that dysregulated mitotic recombination drives the genomic instability underpinning the development of cancer in these individuals. Here we use physical analysis of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
103
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 47 publications
2
103
0
Order By: Relevance
“…Where possible, we compare the rDNA cluster lengths found in surgically excised nearby nontumor tissue to the gene cluster lengths found in the tumor itself, and to gene cluster lengths from the patients' peripheral blood as an additional control (lanes N, T, and B, respectively). Our prior experiences with both human blood and cell lines indicated that analysis of gene cluster lengths from 50 kb to ∼1 Mb is the most informative range for detecting recombination-mediated alterations (3,5), so this is the methodology we followed in this present work. Gene clusters larger than 1 Mb all run together unresolved at the top of the gel in the region (indicated by the ★) under these electrophoretic conditions, otherwise all unique gene clusters shorter than 1 Mb are resolved as individual bands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where possible, we compare the rDNA cluster lengths found in surgically excised nearby nontumor tissue to the gene cluster lengths found in the tumor itself, and to gene cluster lengths from the patients' peripheral blood as an additional control (lanes N, T, and B, respectively). Our prior experiences with both human blood and cell lines indicated that analysis of gene cluster lengths from 50 kb to ∼1 Mb is the most informative range for detecting recombination-mediated alterations (3,5), so this is the methodology we followed in this present work. Gene clusters larger than 1 Mb all run together unresolved at the top of the gel in the region (indicated by the ★) under these electrophoretic conditions, otherwise all unique gene clusters shorter than 1 Mb are resolved as individual bands.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, if a tumor has lost control over recombination, the configuration of gene cluster lengths in the tumor will be different, relative to nontumor cells (5). If the rDNA cluster length restructuring occurred before clonal expansion of the prototumor cell, for example in the lungs of a heavy smoker, the altered length gene clusters will be present in the entirety of the subsequent tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this restructuring was also seen in fibroblasts from Ataxia Telangiectasia and Bloom syndromes, which are known to be caused by mutations in a DNA double strand break repair protein ATM and the BLM Rec Q helicase mentioned above [26,27]. Surprisingly, mutations in the Rec Q helicase WRN, which is implicated in Werner syndrome, did not alter the length of ribosomal DNA clusters [27]. Furthermore, as mentioned previously, the methylation status of the ribosomal DNA promoter and subsequent heterochromatin formation was directly linked to ribosomal DNA stability in a mammalian cell line [38].…”
Section: Introductionmentioning
confidence: 84%
“…For example, in human cancers approximately 50% of lung and colorectal solid tumors demonstrate ribosomal DNA restructuring [26]. Moreover, this restructuring was also seen in fibroblasts from Ataxia Telangiectasia and Bloom syndromes, which are known to be caused by mutations in a DNA double strand break repair protein ATM and the BLM Rec Q helicase mentioned above [26,27]. Surprisingly, mutations in the Rec Q helicase WRN, which is implicated in Werner syndrome, did not alter the length of ribosomal DNA clusters [27].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation